Sex Dilemmas, Amazons and Cyborgs : Feminist Cultural Studies and Sport - Tolvhed, Helena (My University, 2013)
In this article, I discuss sport and physical activities as a field of empirical investigation for feminist cultural studies with a potential to contribute to theorizing the body, gender and difference. Sport has, historically, served to legitimize and rein-force the gender dichotomy by making men “masculine” through developing physical strength and endurance, while women generally have been excluded or di-rected towards activities fostering a “feminine suppleness”. The recent case of runner Caster Semenya, who was subjected to extensive gender tests, demon-strates how athletic superiority and “masculine” attributes in women still today stir public emotions and evoke cultural anxieties of gender blurring. But the rigid gender boundaries have also made sport a field of transgressions. From the “Soviet amazon” of the Cold War, transgressions in sport have publicly demonstrated, but also pushed, the boundaries of cultural understandings of gender. Gender verification tests have exposed a continuum of bodies that cannot easily be arranged into two stable, separate gender categories. In spite of the so called “corporeal turn”, sport is still rather neglected within cultural studies and feminist research. This appears to be linked to a degradation, and fear, of the body and of the risk that women – once again – be reduced to biology and physical capacity. But studies of sport might further develop under-standings of the processes through which embodied knowledge and subjectivity is produced, in a way that overcomes the split between corporeality and discursive regimes or representations. Furthermore, with the fitness upsurge since the 1980s, the athletic female body has emerged as a cultural ideal and a rare validation of “female masculinity” (Halberstam) in popular culture. This is an area well-suited for “third wave” feminist cultural studies that are at ease with complexities and contradictions: the practices and commercialized images of the sportswoman are potentially both oppressive and empowering.
Keywords: 306 Kultur und Institutionen; Cultural studies; history; gender; body; sport; feminist theory